The Effects Of Enzyme Inhibition On The Myristicin Content And The Quality Parameters Of Nutmeg (Myristica Fragrans) Pickles - Ab. Rahman, Nur Ain (2018)
Myristicin, a major compound found in the pericarp of nutmeg (Myristica fragrans) can cause chronic intoxication to fatality to human if consumed over the minimum dose. Alcohol acyltransferase (AAT) enzyme is said to be responsible in the production of myristicin. Soaking nutmeg in a concentrated solution to pickle has been reported to enhance AAT enzyme activities and myristicin content. A fivephase study was undertaken to examine the effects of different preservation treatments on physicochemical properties of pickled nutmeg. Selected commercial nutmeg products were first screened for myristicin content. Subsequently, the effects of soaking in different solutions (NaCl and sucrose) at different concentrations and soaking times on AAT enzyme activities and myristicin content of nutmeg were examined. The effects of blanching treatment and the combination effects of different blanching times and pickling process (5, 7 and 9 minutes, labelled as BP5, BP7 and BP9 respectively) on the same parameter were observed. Physicochemical properties of blanched and non-blanched nutmeg pickles were also studied. The results revealed that commercial nutmeg pickles contained the highest myristicin (2.18 mg/100g). Increased solutes concentrations and times in NaCl and sucrose significantly increased AAT enzyme activities and myristicin content (p < 0.05), notably higher in NaCl solution than in sucrose solution. Increase in blanching time from 0 to 9 minutes significantly reduced AAT enzyme activities and myristicin content in fresh and blanched pericarp, giving 39.034 (fresh) > 3.478 (blanched pericarp) u/mg protein and myristicin 0.451 (fresh) mg/100g to ND (blanched pericarp) respectively. AAT enzyme activities and the production of myristicin were significantly inhibited when pickling process was preceded by blanching. Total phenol content (TPC) and antioxidants analyses showed that blanched pickle nutmeg (BP) had lower antioxidant properties compared to commercial pickle nutmeg (CP) (p > 0.05). Colour analyses indicated no significant difference between the colours of CP, BP5, BP7 and BP9 (p < 0.05) while texture analyses showed that CP had higher texture compared to BP5, BP7 and BP9 (p < 0.05). Microbiological analyses for yeast and mold showed no significant difference between CP, BP5, BP7 and BP9 (p < 0.05). Sensory analyses demonstrated that pickling process improved overall acceptability for blanched pickle as compared to fresh nutmeg. No significant differences were found between CP, BP5 and BP7 for appearance, taste and crunchiness (p > 0.05). The study suggests that blanching treatment was effective in inhibiting AAT enzyme activities, reducing myristicin content to below its toxic level, thus improving the qualities of nutmeg pickle.